2018
DOI: 10.1051/0004-6361/201732092
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine in the solar neighborhood: Chemical evolution models

Abstract: Context. In the light of the new observational data related to fluorine abundances in the solar neighborhood stars, we present here chemical evolution models testing different fluorine nucleosynthesis prescriptions with the aim to best fit those new data. Aims. We consider chemical evolution models in the solar neighborhood testing different nucleosynthesis prescriptions for fluorine production with the aim of reproducing the observed abundance ratios [F/O] [Fe/H]. We study in detail the effects of different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 46 publications
3
66
0
Order By: Relevance
“…The yields needed to increase it instead, are larger than the current best description of the yields from Wolf-Rayet stars and Novea (Spitoni et al 2018), which are, most likely, even overestimated. In order to fit the increasing abundances at high metallicities, Spitoni et al (2018) tried to model the galactic chemical evolution of fluorine by artificially increasing the Wolf-Rayet yields as well as including a fluorine production from novae, which could better model the observed data. Thus, the super-solar fluorine trend can currently not be explained theoretically.…”
Section: Secondary-element Behaviormentioning
confidence: 84%
See 3 more Smart Citations
“…The yields needed to increase it instead, are larger than the current best description of the yields from Wolf-Rayet stars and Novea (Spitoni et al 2018), which are, most likely, even overestimated. In order to fit the increasing abundances at high metallicities, Spitoni et al (2018) tried to model the galactic chemical evolution of fluorine by artificially increasing the Wolf-Rayet yields as well as including a fluorine production from novae, which could better model the observed data. Thus, the super-solar fluorine trend can currently not be explained theoretically.…”
Section: Secondary-element Behaviormentioning
confidence: 84%
“…We find, in principle, a flat [F/Fe] versus [Fe/H] trend for sub-solar metallicities, but an increasing trend above solar metallicities. This increase in [F/Fe] is difficult to explain; even if possible novae and the less likely Wolf Rayet channels are at play for these metallicities, the predicted fluorine production is not enough (Spitoni et al 2018).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The abundances of F and Fe illustrated in Figure 10 can be used to evaluate contributions from possible sources for the nucleosynthesis of 19 F based on chemical evolution model predictions by Timmes et al (1995), Alibés et al (2001), Renda et al (2004), Kobayashi et al (2011a;2011b), Spitoni et al (2018), and Prantzos et al (2018); shown in the bottom panel of Figure 10. Likely sources to consider are both neutrino nucleosynthesis (or the "ν-process"; Woosley et al 1990;Timmes et al 1995;Alibés et al 2001;Kobayashi et al 2011a;2011b) and AGB stars Forestini et al 1992;Abia et al 2009;Cristallo et al 2014;Spitoni et al2018).…”
Section: Comparisons With Chemical Evolution Modelsmentioning
confidence: 99%